2022
DOI: 10.1111/1759-7714.14354
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of ADAMDEC1 correlates with tumor progression and predicts poor prognosis in non‐small cell lung cancer (NSCLC) via the PI3K/AKT pathway

Abstract: Background: ADAM-like decysin-1 (ADAMDEC1) has been reported to play an important role in the pathogenesis of multiple diseases, including cancers. However, its biological role in non-small cell lung cancer (NSCLC) remains largely unknown. Here, we aimed to investigate the biological functions and potential mechanism of ADAMDEC1 in NSCLC. Methods: We verified ADAMDEC1 as a DEG by a comprehensive strategy of TCGA and GEO datasets miming and computational biology. Relative levels of ADAMDEC1 in NSCLC tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Aberrant expression of PI3K signalling pathway is closely related to the process of tumourigenesis [ 34 ]. Lung cancer is the most lethal malignancy in the world, with non-small cell lung cancer (NSCLC) being the most commonly reported histological subtype [ 35 ]. According to reports, new oncogene changes have been discovered in NSCLC, including genetic changes in the PI3K pathway, and PIK3CA mutations in NSCLC may co-occur with epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene homologue (KRAS) and anaplastic lymphoma kinase (ALK) mutations [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant expression of PI3K signalling pathway is closely related to the process of tumourigenesis [ 34 ]. Lung cancer is the most lethal malignancy in the world, with non-small cell lung cancer (NSCLC) being the most commonly reported histological subtype [ 35 ]. According to reports, new oncogene changes have been discovered in NSCLC, including genetic changes in the PI3K pathway, and PIK3CA mutations in NSCLC may co-occur with epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene homologue (KRAS) and anaplastic lymphoma kinase (ALK) mutations [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various biomarkers for diagnosis and prognosis have been identified for NSCLC using the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases, such as ADAM-like decysin-1 ( ADAMDEC1 ), 8 long non-coding RNASEH1-AS1 , 9 sialic acid binding Ig-like lectin 15 ( Siglec15 ), 10 lysine acetyltransferase 2B ( KAT2B ), 11 and Erb-b2 receptor tyrosine kinase 4 ( ERBB4 ). 12 Moreover, many gene signatures have been constructed to predict prognosis and therapeutic response for NSCLC, such as RNA-binding proteins related signature, 13 telomere length-related gene signature, 14 ferroptosis-related long non-coding RNAs signature, 15 immune microenvironment signature, 16 neutrophil extracellular traps-related lncRNA signature, 17 and glycolysis-related gene signature.…”
Section: Introductionmentioning
confidence: 99%
“…For central nervous system tumors, it was found that ADAMDEC1 expression level was significantly higher than the control group in either enamel epithelial craniopharyngioma or squamous papillary craniopharyngioma. ADAMDEC1 is rarely expressed in grade I and grade II gliomas, but highly expressed in grade III and grade IV gliomas ( 26 ). Based on the important roles that ADAMDEC1 played in other cancers, this study investigated the contribution and prognostic signature of ADAMDEC1 in glioma.…”
Section: Introductionmentioning
confidence: 99%